The Role of Job Satisfaction as a Mediator of Work Discipline and Organizational Climate on Employee Performance - Ni Luh Mitha Anggun PARAMITHA; Ni Luh Putu INDIANI; Putu Ngurah Suyatna YASA (PT Keberlanjutan Strategis Indonesia, 2024)
The construction sector plays an important role in the economic growth of a country including Indonesia. In the construction sector, there are very complex operational activities, so it is important to consider factors that can encourage employees to be willing to work optimally for the company. This study analyzes the effect of work discipline and organizational climate on employee performance with job satisfaction as mediation. The object of this research is PT Tunas Jaya Sanur Group, which is one of the largest industrial sectors in Bali, and its projects have spread throughout Indonesia. The sample in this study was taken proportionally to employees especially staff at PT Tunas Jaya Sanur Group. The data collection method is a survey method with a questionnaire. The analysis technique used is inferential analysis technique with Partial Least Square (PLS). The results found that work discipline has a negative and insignificant effect on employee performance, work discipline has a significant positive effect on job satisfaction, organizational climate has a significant positive effect on employee performance, organizational climate has a significant positive effect on job satisfaction, job satisfaction has a significant positive effect on employee performance, job satisfaction partially mediates the relationship between work discipline and employee performance and, job satisfaction partially mediates the relationship between organizational climate and employee performance. This can confirm the two-factor theory that two factors influence a person's motivation in doing something, namely motivational factors and maintenance factors.